1986
DOI: 10.1523/jneurosci.06-11-03152.1986
|View full text |Cite
|
Sign up to set email alerts
|

Competition regulates the efficacy of an identified synapse in crickets

Abstract: The efficacy of the synaptic contact between an identified sensory neuron and an identified interneuron in crickets is increased when neighboring afferent synapses are removed early in postembryonic life. The physiological changes are correlated with changes in the structure of the presynaptic neuron's axonal arborizations: When neighboring axons are destroyed, there is a shift of the remaining axonal arbors into deafferented regions and an increase in the number of putative contacts with the postsynaptic neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
48
0

Year Published

1990
1990
2001
2001

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 29 publications
5
48
0
Order By: Relevance
“…A relationship between the number of synaptic contacts and the size of a synaptic response has been demonstrated in other systems (e.g., Kuno et al, 1971;Korn et al, 1981;Grantyn et al, 1984). A method commonly used to establish this relationship is quanta1 analysis of neurotransmitter release (Korn et al, 1982;Shepherd and Murphey, 1986;Hamon et al, 1990;Laurent and Sivaramakrishnan, 1992). Our working hypothesis predicts that binomial IZ, which is related to the number of synaptic contacts, would decrease during APR's regression.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…A relationship between the number of synaptic contacts and the size of a synaptic response has been demonstrated in other systems (e.g., Kuno et al, 1971;Korn et al, 1981;Grantyn et al, 1984). A method commonly used to establish this relationship is quanta1 analysis of neurotransmitter release (Korn et al, 1982;Shepherd and Murphey, 1986;Hamon et al, 1990;Laurent and Sivaramakrishnan, 1992). Our working hypothesis predicts that binomial IZ, which is related to the number of synaptic contacts, would decrease during APR's regression.…”
Section: Discussionmentioning
confidence: 77%
“…Our working hypothesis predicts that binomial IZ, which is related to the number of synaptic contacts, would decrease during APR's regression. Similar information could potentially be gained by counting the number of synaptic contacts between individual PH afferents and APR using anatomical methods (e.g., Shepherd and Murphey, 1986;Blagburn and Thompson, 1990). Although our hypothesis relating the number of synaptic contacts to EPSP amplitude was formulated to account for developmental changes in EPSP amplitude, it may also account for the relationship between PH position and EPSP amplitude within a developmental stage (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…Considerable evidence supports this latter possibility: afferents with different frequency-tuning properties have been demonstrated to make connections onto the same interneuron (Shepherd and Murphey, 1986;Chiba et al, 1988;Murphey 1993, 1994). Murphey (1993, 1994) suggested that a single afferent can connect to two different interneurons yet make synapses with very different properties: either habituating or facilitating.…”
Section: Extraction Of Information From Map By Interneurons: Two Diffmentioning
confidence: 99%
“…The invertebrate CNS has long been viewed as having a rigid stereotypic organization that precludes much plasticity (see Murphey, 1986). In recent years, however, studies of long-term physiological and anatomical changes in Aplysia during behav-ioral conditioning (Kandel et al, 1986;Bailey and Chen, 1988a,b), as well as studies of regeneration (Murphey and Lemere, 1984;Shepherd and Murphey, 1986;Loer et al, 1987;Loer and Kristan, 1989) have changed this view.…”
Section: An Anatomicalmentioning
confidence: 99%
“…In recent years, however, studies of long-term physiological and anatomical changes in Aplysia during behav-ioral conditioning (Kandel et al, 1986;Bailey and Chen, 1988a,b), as well as studies of regeneration (Murphey and Lemere, 1984;Shepherd and Murphey, 1986;Loer et al, 1987;Loer and Kristan, 1989) have changed this view. Instead, it has become apparent that, even though the behavioral repertoire of invertebrates is less complex than that of vertebrates, developmental and physiological plasticity is a common feature (reviewed in Lnenicka and Murphey, 1989; see also Technau, 1984;Meinertzhagen, 1989).…”
Section: An Anatomicalmentioning
confidence: 99%